แนวทางการพัฒนาการมีส่วนร่วมการดูแลผู้สูงอายุของเทศบาลตำบลสมเด็จ อำเภอสมเด็จ จังหวัดกาฬสินธุ์: ผลการวิจัยเชิงสำรวจ - สมคะเณย์, จินดารัตน์ (Journal of Graduate School of Commerce-Burapha Review, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อสำรวจสภาพการมีส่วนร่วมการดูแลผู้สูงอายุของเทศบาลตำบลสมเด็จ ปัญหา การมีส่วนร่วมการดูแลผู้สูงอายุของเทศบาลตำบลสมเด็จ และแนวทางการพัฒนาการมีส่วนร่วมการดูแลผู้สูงอายุ ของเทศบาลตำบลสมเด็จ เป็นการศึกษาวิจัยเชิงสำรวจ (Survey research) ประชากรที่ใช้ศึกษาวิจัย ได้แก่ ผู้สูงอายุ ในเขตเทศบาลตำบลสมเด็จ จำนวน 727 คน โดยเก็บรวบรวมข้อมูลจากแบบสอบถามจากกลุ่มตัวอย่าง จำนวน 257 คน คำนวณโดยใช้สูตร Taro Yamane ผู้วิจัยได้ข้อมูลที่ได้มาวิเคราะห์โดยใช้วิธีการแจกแจงความถี่และการหาค่าร้อยละ จากนั้นจึงนำเสนอข้อมูลในรูปตารางประกอบคำบรรยาย ผลการศึกษาครั้ง นี้พบว่าผู้ตอบแบบสอบถามส่วนใหญ่เป็น เพศชาย โดยมีอายุระหว่าง 61 – 70 ปี ซึ่ง มีวุฒิการศึกษา ระดับต่ำกว่าปริญญาตรี และมีสถานภาพเป็นผู้นำชุมชนหรือผู้สูงอายุ แนวทางการพัฒนาการมีส่วนร่วมการดูแลผู้สูงอายุของเทศบาลตำบลสมเด็จคือ องค์กรปกครองส่วนท้องถิ่น ต้องเข้ามามีส่วนร่วมดูแลผู้สูงอายุร่วมกันในชุมชน ควรจัดให้มีอาสาสมัครดูแลผู้สูงอายุอยู่ที่บ้าน พัฒนาสภาพแวดล้อม ที่ปลอดภัยและเสริมสร้างศักยภาพของชุมชนที่ดำเนินการของชมรมผู้สูงอายุ คนต้นแบบ และครอบครัวที่เข้มแข็ง ส่วนสภาพการมีส่วนร่วมการดูแลผู้สูงอายุของเทศบาลตำบลสมเด็จคือ การส่งเสริมด้านกิจกรรม เช่น การส่งเสริมสุข ภาพ การส่งเสริมนันทนาการ การส่งเสริมอาชีพ รวมทั้งการบริการผู้สูงอายุ รองลงมาคือ ด้านการประสานงาน เช่น การติดต่อสื่อสาร การประสานงานกับกลุ่มผู้สูงอายุ องค์กรรัฐหรือเอกชน สำหรับปัญหาการมีส่วนร่วมการดูแลผู้สูงอายุ ของเทศบาลตำบลสมเด็จคือ ปัญหาด้านสวัสดิการสุขภาพอนามัย เช่น การตรวจสุขภาพประจำปี หรือการบริการ หน่วยแพทย์เคลื่อนที่ รองลงมาคือ ปัญหาด้านสวัสดิการนันทนาการ เช่น ชมรมผู้สูงอายุ สถานที่ออกกำลังกายหรือ พักผ่อน รวมถึงกิจกรรมพบปะกัน MEASURES TO ENCOURAGE COOPERATION IN SENIOR CITIZENS CARE TAKING OF SOMDEJ SUBDISTRICT, KALASIN PROVINCE: A SURVEY RESEARCH Chindarat Somkhane Faculty of Political Science and Law, Kalasin Rajabhat University, Kalasin 46230,Thailand This research aims at researching on the state and background of senior citizens’care taking of Somdej subdistrict; its problems and measures to strengthen cooperation. It is a survey research. The population used in this research is 727 senior citizens within the area of Somdej Subdistrict; samples were gathered from 257 sampling population and calculated by TARO Yamane. The researcher analysed such data by distributing its frequency and allocating percentile, then presented them in tables and explanation. Results of this study revealed that most respondents were male aged between 61-70 with lower than bachelor’s degree educational background, and with status of community leaders or the alders. Measures to develop participation in care taking of the elders of Somdej Subdistrict municipality are that the local authority must participate and involve with the community, there should be volunteers to take care of the elders in their homes, safe environment should be developed and the capabilities of the communities which handle the elders should be strengthened. There should also be a role model and strong families. Involvement of care taking of Somdej subdistrict municipality are different types of activities such as health care, recreation activities, vocational promotion together with services to the elders. Next is coordination such as communicating and coordinating with groups of elders, public or private sector. As of the problem of participation in this case, there was one with health care welfare such as a yearly health check or mobile health units, next to this is a problem of recreation for example : the elders clubs, gyms or resting areas together with activities for them to get together.